An Exploratory Analysis of Differential Item Functioning and Its Possible Sources in a Higher Education Admissions Context. Issue 1 (2nd January 2018) - Elena Oliveri, Maria; Lawless, Rene; Robin, Frederic; Bridgeman, Brent
ABSTRACT: We analyzed a pool of items from an admissions test for differential item functioning (DIF) for groups based on age, socioeconomic status, citizenship, or English language status using Mantel-Haenszel and item response theory. DIF items were systematically examined to identify its possible sources by item type, content, and wording. DIF was primarily found in the citizenship group. As suggested by expert reviewers, possible sources of DIF in the direction of U.S. citizens was often in Quantitative Reasoning in items containing figures, charts, tables depicting real-world (as opposed to abstract) contexts. DIF items in the direction of non-U.S. citizens included "mathematical" items containing few words. DIF for the Verbal Reasoning items included geocultural references and proper names that may be differentially familiar for non-U.S. citizens. This study is responsive to foundational changes in the fairness section of the Standards for Educational and Psychological Testing, which now consider additional groups in sensitivity analyses, given the increasing demographic diversity in test-taker populations.